A STUDY ON NOOTROPIC ACTIVITY OF CELASTRUS PANICULATA WILLD WHOLE PLANT METHANOLIC EXTRACT IN RATS - Jakka, Anantha Lakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The objective of the present study was to evaluate the nootropic activity of Celastrus paniculata Willd whole plant methanolic extract (CPPME) using different models. Methods: Nootropic activity in rats with the treatment of CPPME (100, 200, 400 mg/kg, oral.) and piracetam (200 mg/kg, i.p.) were administered to different groups of rats. Effect of drugs on learning and memory of rats was evaluated using elevated plus maze, morris water maze on scopolamine, and aluminum-induced amnesia models, and also estimated the brain acetylcholinesterase (AChE) concentration and the percentage of inhibition of AChE. Results: CPPME shows significantly improved in learning and memory of rats, as indicated by the decline in transfer latency using elevated plus maze and also decrease in escape latency during training and retrieval using morris water maze. Memory-enhancing activity of CPPME (100, 200, 400 mg/kg, oral.) was comparable to piracetam (200 mg/kg, i.p.). CPPME, Mentat (Nootropic Herbal formulation), and piracetam also notably reduced brain AChE concentration and increased the percentage of inhibition of AChE activity in rat brain. Conclusion: Thus, CPPME showed nootropic activity in rats probably by inhibiting brain AChE activity. Keywords: Nootropic activity, Celastrus paniculata Willd whole plant, Methanolic extract, Scopolamine-induced amnesia, Aluminum-induced amnesia, Spatial memory in Morris water maze test and acetylcholinesterase enzyme.